Moda e masculinidade: breves apontamentos sobre o homem dos séculos XX e XXI (ModaPalavra e-periódico, 2011)
Modern society is a fertile land to the condition of individual-consumer. Therefore, we live in a new world organized around images, which radically transform our life experiences, create new identities and multiple possibilities for individual action, allowing it to act as social actor. This article raises some dialogue between fashion and masculinity, their interference in social movements and historical. In addition to treating your modifications mediated by consumption, transforming the aesthetic and symbolic values within a system of social hierarchy and self-construction.